Relationship between Procalcitonin Levels (PCT) and Disease Severity in Hospitalized Patients Confirmed Positive for COVID-19 - Fajrunni'mah, Rizana; Rada, Fransiska; Widhyasih, Retno Martini (JURNAL INFO KESEHATAN, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This disease attacks the respiratory tract and spreads rapidly almost throughout the world, hence, WHO has declared COVID-19 as a global pandemic. The presence of inflammation and bacterial co-infection in COVID-19 hospitalized patients can increase procalcitonin (PCT) levels as a biomarker of inflammation. Elevated PCT levels are also associated with disease severity. The objective of this study is to determine the relationship between PCT levels and disease severity in hospitalized patients who are confirmed positive for COVID-19. This research method is analytic observational with cross sectional design. The sample is in the form of medical record data for 180 COVID-19 patients who are hospitalized at Bhayangkara Tk. I Raden Said Sukanto Hospital, Jakarta for the period July-December 2020. The relationship between PCT levels and disease severity was statistically analyzed using the Chi Square test. The results of this study were 109 (60.6%) men and 71 (39.4%) women with the highest age group being 46-59 years. The average PCT level was 10.38 ng/mL with the lowest level of 0.01 ng/mL and the highest level of 282.00 ng/mL. PCT levels <0.5 ng/mL were discovered in 111 patients (61.7%) and PCT levels 0.5 ng/mL in 69 patients (38.3%). The severity of disease in mild-moderate illness was 87 patients (48.4%), severe was 35 patients (19.4%), and critical was 58 patients (32.2%). The Chi Square test showed that there was a relationship between PCT levels and disease severity in COVID-19 patients (p = 0.000). The higher the PCT level, the higher the severity of the disease, thus, PCT can be used as an indicator to see the severity of the disease.